Optimalisasi Produktivitas Cabai dengan Pestisida Alami Bunga Telang di Nagari Panyalaian - Zahra Ramadhani; Elda Herlina (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The community service was conducted in Jorong Koto Tuo, Nagari Panyalaian, X Koto Subdistrict. This village is located in a mountainous area, where the majority of the population relies on farming as their livelihood. One of the main issues faced by farmers is the attack of pests and diseases on chili plants (Capsicum annuum), which often reduce productivity. The excessive use of chemical pesticides has led to negative impacts on health and the environment. Therefore, an environmentally friendly alternative is needed, one of which is utilizing butterfly pea flowers (Clitoria ternatea L) as a natural pesticide. The community service method includes socialization and training on the preparation and application of natural pesticide made from butterfly pea flower extract. The stages of the activity include preparation, implementation, and evaluation. The results of the community service show that the application of natural pesticide from butterfly pea flowers is effective in reducing pest and disease attacks on chili plants during the two-week observation period, as indicated by the healthy condition of the plants without signs of damage. This service also successfully enhanced the community's understanding of alternative natural pesticides that are safe and environmentally friendly, while also providing the potential to increase chili productivity in Nagari Panyalaian.